Edupreneurship Excellence: Improving Student Morale and Performance Through Sustainable Strategies in the UM German Language Education Study Programme - Prameswari, Pradypta; Erin Alida Damayanti; Thomas Gerald Billion Sambuaga; Indriwardhani, Sri Prameswari (Nexus Publishing NXP, 2024)
Abstract Edupreneurship, also known as entrepreneurship education, is an important and rapidly growing field of research. It makes significant contributions in understanding global and national trends as well as in formulating educational policies and measures for the future. One effective way to facilitate student learning in the context of entrepreneurship education is to implement a project-based learning model. This model encourages creativity and innovation and prepares the skills needed to face the Society 5.0 era. This research focuses on how learning media products can be used as a tool to improve student performance. Accordingly, this study aims to understand how learning media can affect student performance and how it can be used to improve the quality of education in the German Language Education study program at the State University of Malang. It also seeks to explore how sustainable strategies can be implemented in this context to ensure that improvements in student performance can be sustained in the long term. In addition, this research also attempted to understand how student morale could be improved through the implementation of these strategies. As such, this research has comprehensive and multifaceted objectives in an effort to improve the quality of education in Indonesia. This research uses a qualitative approach to understand the research phenomenon and its influencing factors in depth. The research design is experimental, with data collection techniques such as interviews, observations, documentation studies, questionnaires, and focus groups. The data were analyzed using the 6P simultaneous technique. This research has the potential to significantly contribute to the development of entrepreneurial skills, innovation, and academic performance of students in the Department of German Literature. Keywords: Edupreneurship, Learning media, Entrepreneurship education, German language